Distressed firms, zombie firms and zombie lending: A taxonomy - Álvarez, Laura; García-Posada, Miguel; Mayordomo, Sergio (Journal of Banking & Finance, 2023)
This papers develops a taxonomy of financially distressed and zombie firms using a rich dataset that combines detailed firm-level and bank-firm level information in Spain. A distressed firm exhibits both cash-flow and balance-sheet insolvency whereas a zombie firm is a distressed company that has received new credit. We carry out several analyses to test the validity of these definitions. For instance, we document that being distressed is negatively correlated with the probability of receiving new credit. However, the main bank of a distressed firm is more reluctant to restrict the credit supply to this firm than a bank with no previous exposure to the company, which might reflect the incentives of the former to engage in loan evergreening. This financial support contributes to keep zombie firms afloat for a longer period than distressed firms. Moreover, the contraction in capital, employment and sales is much larger in distressed firms than in zombie firms.